Pengaruh Daun Salam (Syzygium polyanthum) terhadap Protein Kuning Telur, Total Fenol dan Flavonoid pada Telur Asin - Ria Marsella; Imam Thohari; Lilik Eka Radiati (Faculty of Animal Science Universitas Brawijaya, 2016)
The purpose of this research was to evaluate the effect of addition of boiled of bay leaf liquid on the salty egg. Variables were egg yolk protein, phenol total and flavonoids, and to find out the best treatment of addition of boiled of bay leaf liquid on the salty egg. The method used an experiment with a complete randomized design, 5 treatments and 4 replication. The treatment were P0 (control), P1 (5% addition of boiled of bay leaf liquid), P2 (10% addition of boiled of bay leaf liquid), P3 (15% addition of boiled of bay leaf liquid), P4 (20% addition of boiled of bay leaf liquid). The research results showed that boiled of bay leaf liquid gave a significant different result in increasing the content of total phenols and flavonoid as for the egg yolk protein give effect not different real. 20% addition of boiled of bay leaf liquid was the best treatment reviewed from egg yolk protein 17.88±1.70 phenol total 0.064±0.003 and flavonoids 92.62±1.92 suggestion from this research was salted egg added boiled of bay leaf liquid with higher concentration to know the physical quality of salted eggs.